FLOOD RISK MANAGEMENT: IMPLEMENTATION OF THE EUROPEAN DIRECTIVE 2007/60/EC IN THE AUTONOMOUS REGION OF MADEIRA - Mileu, Nelson (2019)
The Decree-Law no. 115/2010, of October 22 where the Directive 2007/60/EC of the European Parliament and of the Council of 23 October 2007 on the assessment and management of flood risks is transposed into Portuguese national law, establish a framework for the assessment and management of flood risks. Flash floods and debris events have a long history in Madeira Island resulting in several adverse impacts on human health, environment, cultural heritage and economic activity. For this reason and since the catastrophic debris event of 20 February 2010 the establishment of flood risk management plan in Autonomous Region of Madeira assumes a double importance. The aim of the paper is to present flood risk analysis methods and technical options adopted in the elaboration of flood hazard and flood risk maps as well the flood risk management plan strategy. For showing the principles and stages of Flood Risk Directive implementation in the Autonomous Region of Madeira, Socorridos watershed is used as case study. Nevertheless some limitations associated with the volcanic mountain island characteristics and the debris events specificities, the flood risk analysis methods used are in harmony with the requirements of the Flood Risk Directive. Another important issue is the flood risk management plan strategy that addresses all aspects of flood risk management.